Women in dentistry: A perspective on major universities in Saudi Arabia. Part 1: Historical background - Randa E. Shaker; Amani A. Babgi (Saudi Dental Journal)
As the works of females have been present in many fields of our lives, the history mentions little trace of these facts. The field of dentistry was among these professions. This paper will review the presence of dental practice by women world wide and will present a review of dentistry in Saudi Arabia. Keywords: Saudi Arabia, Universities, Dentistry, Women, History